Model Pelayanan Sektor Pemerintah Daerah Sumatera Barat pada Dinas Kependudukan dan Pencatatan Sipil Kota Pariaman - Dasman Lanin; Syamsir Syamsir; Aziza Bila (Journal of Education on Social Science (JESS), 2019)
Local governments have the duty to provide good services to the community in order to realize the country's goals in realizing public welfare. To realize these goals, local governments must hold governments that satisfy customers. However, the implementation of innovations based on Total Quality Management has not yet reached the level of perfect solutions. By realizing this, we need a service model that is able to provide satisfaction to customers both internal and external customers. This study aims to examine the service model of the West Sematera regional government sector. The study was conducted using quantitative approach with a survey strategy. Data was collected using a questionnaire instrument that has been tested for validity and reliability. The study population was all employees (internal customers) and the public (external customers) who used the Pariaman City Population and Civil Registry Service. The research sample amounted to 225 respondents. For internal customers determined using saturated sample techniques. Whereas external customers are determined using proportional stratified random sampling. Data that has been collected is processed using t-test and multiple regression. This study states that the service model that has been tested can be used to measure customer satisfaction both internally and externally.